Genomic and protein expression analysis reveals flap endonuclease 1 (FEN1) as a key biomarker in breast and ovarian cancer. Issue 7 (13th May 2014) - Abdel-Fatah, Tarek M.A.; Russell, Roslin; Albarakati, Nada; Maloney, David J.; Dorjsuren, Dorjbal; Rueda, Oscar M.; Moseley, Paul; Mohan, Vivek; Sun, Hongmao; Abbotts, Rachel; Mukherjee, Abhik; Agarwal, Devika; et al.
Abstract : FEN1 has key roles in Okazaki fragment maturation during replication, long patch base excision repair, rescue of stalled replication forks, maintenance of telomere stability and apoptosis. FEN1 may be dysregulated in breast and ovarian cancers and have clinicopathological significance in patients. We comprehensively investigated FEN1 mRNA expression in multiple cohorts of breast cancer [training set (128), test set (249), external validation (1952)]. FEN1 protein expression was evaluated in 568 oestrogen receptor (ER) negative breast cancers, 894 ER positive breast cancers and 156 ovarian epithelial cancers. FEN1 mRNA overexpression was highly significantly associated with high grade (p = 4.89 × 10−57), high mitotic index (p = 5.25 × 10−28), pleomorphism (p = 6.31 × 10−19), ER negative (p = 9.02 × 10−35), PR negative (p = 9.24 × 10−24), triple negative phenotype (p = 6.67 × 10−21), PAM50.Her2 (p = 5.19 × 10−13), PAM50. Basal (p = 2.7 × 10−41), PAM50.LumB (p = 1.56 × 10−26), integrative molecular cluster 1 (intClust.1) (p = 7.47 × 10−12), intClust.5 (p = 4.05 × 10−12) and intClust. 10 (p = 7.59 × 10−38) breast cancers. FEN1 mRNA overexpression is associated with poor breast cancer specific survival in univariate (p = 4.4 × 10−16) and multivariate analysis (p = 9.19 × 10−7). At the protein level, in ER positive tumours, FEN1 overexpression remains significantly linked to high grade, high mitotic index and pleomorphism (ps < 0.01). In ER negative tumours, high FEN1 is significantly associated with pleomorphism, tumour type, lymphovascular invasion, triple negative phenotype, EGFR and HER2 expression (ps < 0.05). In ER positive as well as in ER negative tumours, FEN1 protein overexpression is associated with poor survival in univariate and multivariate analysis (ps < 0.01). In ovarian epithelial cancers, similarly, FEN1 overexpression is associated with high grade, high stage and poor survival (ps < 0.05). We conclude that FEN1 is a promising biomarker in breast and ovarian epithelial cancer. Highlights: FEN1 has key roles in Okazaki fragment maturation during replication and long patch DNA base excision repair. FEN1 mRNA and protein expression was comprehensively evaluated in large cohorts of breast cancers. FEN1 mRNA and protein overexpression is an adverse prognostic and predictive biomarker in breast cancer. FEN1 was investigated in ovarian cancer and FEN1 protein overexpression has prognostic and predictive significance.